(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sustainable agriculture, the agronomic practices promoting consistent food security and environmental conservation, has extremely low adoption rates in developing countries. This conundrum may be resolved by identifying the barriers faced by farmers in adopting various SAPs which make them inaccessible and reduce their backing significantly in a lower-middle-income country like India. A literature review was conducted for (1) Understanding the concept of sustainable agriculture (2) Identifying and reviewing the principal challenges in wide-scale adoption of SAPs in India (3) Critical analysis of existing initiatives by the government and possible solutions. The foremost challenges include: decreased productivity and profits, lack of awareness and guidance, lack of technology and infrastructure and the question of long-term generation of employment. It is felt that appropriate information dissemination, technological and infrastructural advancements along with schemes distinctly catered to states should be devised in order to encourage and expedite the adoption process.